2020
DOI: 10.1108/ramj-05-2020-0017
|View full text |Cite
|
Sign up to set email alerts
|

Factors determining bank deposit growth in Turkey: an empirical analysis

Abstract: Purpose This paper aims to examine the key factors determining bank deposit growth in Turkey for the period 2000Q1–2016Q4. Design/methodology/approach The study employs the autoregressive distributed lag approach to investigate the effect of bank-level and macroeconomic factors on deposit growth. Findings The results reveal that bank stability, banking sector efficiency, broad money supply, economic growth, and inflation are significant determinants of deposit growth in the long run. The findings further s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

4
16
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(26 citation statements)
references
References 16 publications
4
16
0
Order By: Relevance
“…Another stream of literature has investigated the impact of inflation rates (CPI) on the deposits' behavior of banking, (e.g. Touny, 2008;Harald & Heiko, 2009;Gemedu, 2012;Khaskheli et al, 2013;Islam et al, 2019;Yakubu & Abokor, 2020); The empirical findings of these studies are not conclusive, as they show mixed evidence regarding their impact on deposits' behavior of banks. For instance, (Hadiyanto & Haryanto, 2013), concluded that there is no causal relationship between the inflation rate and time deposits.…”
Section: The Relationship Between the Inflation Rate (Cpi) And Deposi...mentioning
confidence: 99%
See 2 more Smart Citations
“…Another stream of literature has investigated the impact of inflation rates (CPI) on the deposits' behavior of banking, (e.g. Touny, 2008;Harald & Heiko, 2009;Gemedu, 2012;Khaskheli et al, 2013;Islam et al, 2019;Yakubu & Abokor, 2020); The empirical findings of these studies are not conclusive, as they show mixed evidence regarding their impact on deposits' behavior of banks. For instance, (Hadiyanto & Haryanto, 2013), concluded that there is no causal relationship between the inflation rate and time deposits.…”
Section: The Relationship Between the Inflation Rate (Cpi) And Deposi...mentioning
confidence: 99%
“…Several studies reveal the effect of inflation rates on the mobilization of savings and on the deposits' behavior of banking, (e.g. Touny, 2008;Harald & Heiko, 2009;Abduh & Sukmana, 2011;Gemedu, 2012;Ngula, 2012;Khaskheli et al, 2013;Rama & Kassim, 2013;Abdul Karim et al, 2014;Abou El-Seoud, 2014;Mashamba et al, 2014;Larbi-Siaw & Lawer, 2015;Tareq, 2015;kapounek et al, 2016;Akhtar et al, 2017;Mushtaq & Siddiqui, 2017;Arikewuyo & Akingunola, 2019;Menza, 2019;Tho'in & Prastiwi, 2019;Toriola, 2019;Agwu et al, 2020;Ünvan & Yakubu, 2020;Yakubu & Abokor, 2020). For instance, (Obi & Ezeanyeji, 2019) point out that the inflation rate has an insignificant positive effect on savings mobilization.…”
Section: The Relationship Between the Inflation Rate (Cpi) And Deposi...mentioning
confidence: 99%
See 1 more Smart Citation
“…(Jokipii & Monnin, 2013). Banks obtain funds from the public through deposits, current accounts, and savings (Yakubu & Abokor, 2020). The table above illustrates that in recent years, the government always experienced a deficit from the state budget (Dirgahayu et al, 2021).…”
Section: Introductionmentioning
confidence: 99%
“…
Deposit mobilization is one of the key activities that contribute to the efficiency of banks (Yakubu, 2020) Being in the sixty-first place in the emerging economics market list out of sixty-six countries, deposits are important for Sri Lankan bank operations. Many businesses rely seriously on bank loans as a source of financing.
…”
mentioning
confidence: 99%